AnalisaTingkat Kepuasan Mahasiswa Terhadap Layanan Pembelajaran Menggunakan K-Means dan Algoritma Genetika - Ade Rizki Rinaldi; Lana Surlanto; Dadang Sudrajat; Dian Ade Kurnia (STMIK IKMI Cirebon, 2019)
The level of student satisfaction with learning services in higher education is one factor in the quality of college learning. To determine the level of student satisfaction with learning services in higher education, it is necessary to analyze the level of student satisfaction with learning services. K-Means method is a technique of grouping data based on the level of similarity of each member. K-Means can be used to classify the student satisfaction index on learning services. The K-Means method can also be optimized with genetic algorithms to determine the best centroid value. K-means optimization with Genetic Algorithms can be used as a technique to determine the level of student satisfaction with learning services. Obtained by Davies Bouldien Index from the K-Means and Genetics method is 1.593 with cluster number 5